The Influence of Company Reputation, Compensation and Work Environment on Interest in Applying for Jobs (Study of Abfii Perbanas Alumni, Management Department) - Pratiwi, Ajeng; Widyarsih, Rahajeng (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2024)
This study aims to determine how the influence of company reputation, compensation and work environment on the interest in applying for a case study job at ABFII Perbanas alumni majoring in management. The data analysis methods used are Validity Test, Reliability Test, Classical Assumption Test, Determination Coefficient Test, Statistical Test, and multiple linear regression analysis. The population of this study were alumni of ABFII Perbanas majoring in management in 2018, the sample used in this study amounted to 62 people. The data collection method used is by using a questionnaire distribution technique. The type of research used is a descriptive analysis method with a quantitative approach assisted by SPSS version 18 data processing tools. The results show that there is a significant influence between variables company reputation, salary, and work environment simultaneously on variables interested in applying for job.